Lama Menyusui Dan Tingkat Kemiskinan Keluarga Kaitannya Dengan Kejadian Stunting Pada Anak Balita : Studi Literatur - Lusyana Gloria Doloksaribu; Efendi S Nainggolan; Tiurlan Mariasima Doloksaribu (POLTEKKES KEMENKES MEDAN, 2022)
Background Stunting is one of the nutritional problems faced in today's world that many toddlers experience. Stunting is a condition where children under five have a length / height that is less when compared to age. The incidence of stunting arises from conditions such as poverty and inappropriate breastfeeding. The aim of the study was to determine the relationship between length of breastfeeding and the level of family poverty with the incidence of stunting in children under five in a literature study. The type of research used is a literature study with secondary data collection from scientific research articles from 2015-2020. Article selection is done by setting inclusion and exclusion criteria consisting of duplication, title, abstract and PICOS criteria. Search data using the online Google Scholar, DOAJ, PubMed and Garuda databases using the key words